IMPROVING SPEAKING ABILITY IN PROCEDURE TEXT BY USING RETELLING TECHNIQUE - Nursanti, Eka; Susilawati, Endang; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The purpose of this classroom action research is to improve students speaking ability by using retelling technique. This research focus on fluency, accuracy and comprehension. The subject of the research was the tenth grade students of SMA Negeri 1 Sukadana. The tools of data collection used were oral test, field note and observation checklist. In the first cycle, the data could not be assessed because it was not like researcher expected. In the second cycle there were 56,7% srtudents passed and raised became 83,3% in the third cycle. Based on the data taken from the three cycles, it was found that the students fluency, accuracy and comprehension of their speaking improved from cycle to cycle. Keywords: speaking ability, procedure text, retelling technique Abstrak: Tujuan dari penelitian tindakan kelas ini yaitu untuk meningkatkan kemampuan berbicara siswa. Fokus penelitian ini adalah kelancaran, ketelitian dan pemahaman. Subjek penelitian ini adalah siswa kelas X di SMA Negeri 1 Sukadana. Alat yang digunakan dalam pengumpulan data adalah oral test, field note, dan observation checklist. Pada siklus pertama, data yag diperoleh tidak dapat di nilai karena hasilnya tidak sesuai dengan yang diharapkan peneliti. Pada siklus kedua, ada 56,7% siswa tuntas danmeningkat menjadi 83,3% pada siklus ketiga. Berdasarkan data yang di ambil dari ketiga siklus, telah ditemukan bahwa kelancaran, ketelitian dan pemahaman siswa dalam berbicara meningkat dari siklus ke siklus. Kata kunci: kemampuan berbicara, teks prosedur, teknik bercerita